Playing with the past: the politics of historiographic theatre - Haddow, Sam (2013)
This thesis explores theatre's capacity to act as a medium for the 'production' of history. Proposing a theoretical model capable of accommodating this significantly underexplored function of contemporary drama, I adapt recent developments in the debates over textual historiography to the processes of theatrical production. Concurrent with this investigation, I examine certain examples of one of the most popular forms of contemporary historical theatre in Britain - the documentary strand known as 'verbatim' - and demonstrate the ways in which a lack of attention to theatre- historiography has allowed some uninformed and unstable historical methodologies to proliferate in theatrical discourses. Initially focussing upon the August Riots of 2011, I demonstrate the ways in which the political disingenuousness of key verbatim methodologies renders them unfit to engage productively with the demands of their surrounding context. Arguing the necessity for theatre to fulfil this societal function, I then consider alternative, politically conscious theatrical approaches to history.